Femoral vascular access-site complications in the cardiac catheterization laboratory: diagnosis and management. (August 2011) - Bhatty, Shaun; Cooke, Richard; Shetty, Ranjith; Jovin, Ion S
Vascular access-site complications remain a major cause of morbidity and mortality with cardiac catheterization and percutaneous intervention using the femoral approach. Complications may be divided into major and minor. Major complications include bleeding that requires transfusion, retroperitoneal hemorrhage and nonhemorrhagic complications such as pseudoaneurysm, arteriovenous fistula, arterial dissection, thrombosis and limb ischemia. Minor complications include minor bleeding, ecchymosis and hematomas. The incidence of access complications varies by the population studied. Numerous patient-related and procedure-related risk factors have been associated with vascular access-site complications. Alternate access sites, the use of fluoroscopic guidance, focus on anticoagulant and antiplatelet therapy, and arterial closure devices are all methods being investigated to prevent and reduce complications. History and physical examination are important in identifying vascular access-site complications and imaging is helpful to confirm the diagnosis.